FLAVONOLS AND AN OXYCHROMONOL FROM PILIOSTIGMA RETICULATUM - Mabusela, W. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The leaf extract from the plant Piliostigma reticulatum was found to exhibit antimicrobial activity against some bacteria and fungi such as Staphylococcus aureus (NCTC 6571), Escherichia coli (NCTC 10418), Bacillus subtilis (NCTC 8236), Proteus vulgaris (NCTC 4175), Aspergillus niger (ATCC 10578) and Candida albicans (ATCC 10231). Upon investigation of the chemical constituents present in the leaf extract, a total of seven compounds were isolated and their structures were unambiguously established by spectroscopic methods including HR-MS and NMR spectrometry. Four of the isolated compounds were novel, namely 6-C-methyl-2-p-hydroxyphenyloxychromonol (piliostigmol) (1), 6,8-di-C-methylquercetin-3,3’,7–trimethylether (2), 6,8-di-C-methylquercetin-3,3’-dimethylether (3) and 3’,6,8,-tri-C-methylquercetin-3,7-dimethylether (4). The other three were known C-methylated flavonols and they were isolated from P. reticulatum for the first time. These were 6-C-methylquercetin-3-methylether (5), 6,8-di-C-methylkaempferol-3-methylether (6) and 6-C-methylquercetin-3,3’,7-trimethylether (7). All the isolated compounds were tested for cytotoxicity using the brine shrimp toxicity assay and all of them were active albeit at different levels. With respect to the antibacterial activity, piliostigmol (1) showed the highest activity against E. coli (MIC = 2.57 µg/ml, 0.006 mmol), which is three times more that of amoxicillin, whereas 4 and 7 showed the least activity.